Antibody based conditioning for allogeneic hematopoietic stem cell transplantation - Saha, Asim; Blazar, Bruce R. (Frontiers in Immunology, 2022)
Allogeneic hematopoietic stem cell transplantation (allo-HSCT) is a curative therapeutic option for many patients with hematological malignancies and nonmalignant hematopoietic disorders. To achieve stable engraftment of donor hematopoietic stem cells (HSCs), recipient HSC deletion is needed to create space for incoming donor HSCs and donor HSCs must escape immune rejection by the recipient. Conventional allo-HSCT requires high dose of irradiation and/or chemotherapy to produce sufficient host stem cell and immune system ablation to permit donor HSC engraftment. However, these procedures also result in nonspecific tissue injury that can cause short- and long-term adverse effects as well as incite and amplify graft-versus-host-disease (GVHD). The delivery of targeted radiotherapy to hematopoietic tissues with the use of a radioimmunoconjugate (RIC) as a part of transplant preparative regimen has shown clinical benefits. RIC clinical data provide evidence for decreased relapse without increased transplant-related mortality by delivering higher targeted radiation to sites of malignancy than when given in a nontargeted fashion. An alternative approach to allo-HSCT has been developed and tested in preclinical mouse models in which nonmyeloablative preconditioning with low dose of the alkylating agent (busulfan) or lower systemic dose of irradiation combined with co-stimulatory pathway blockade (CTLA4-Ig, anti-CD40L monoclonal antibody) and/or immunosuppressive drugs have been used. Under these conditions, mixed chimerism and transplantation tolerance to fully MHC mismatched donor marrow was observed. Recently, several novel proof-of-concept antibody-mediated preconditioning methods have been developed that can selectively target hematopoietic stem and immune cells with minimal overall toxicity. Antibody-drug-conjugate (ADC) combined with reduced intensity conditioning or high dose ADC as single dose monotherapy have shown promise for allo-HSCT in preclinical models. The purpose of the current review is to discuss the literature exploring antibody-based conditioning that includes native antibody, radiolabeled antibody conjugates, and ADC for allo-HSCT.